Analisis Karakter Siswa Kelas 1 Saat Pembelajaran Menulis Huruf Tegak Bersambung di SDN Jelegong 01 Rancaekek - Silvia Agustini; Yayang Furi Furnamasari (Pusat Riset dan Inovasi Nasional, 2023)
This research is motivated by the results of observations and experiences of researchers, that in a lesson you will definitely find various student characters. One of them is learning to write cursive letters. This study aims to analyze the character of class I students when learning to write cursive letters at SDN Jelegong 01 Rancaekek. This study used a qualitative descriptive method with data collection using literature study as well as direct observation when learning to write cursive letters took place in class I SDN Jelegong 01 Rancaekek. Based on the results of observations, researchers found various characters shown by students when learning to write cursive letters took place. Among them, there were those who refused to write cursive letters and chose to write in printed letters, some did not even want to write at all and not a few students were happy when this learning was carried out. The need for teacher guidance to students who do not master these skills is one reason that needs more attention. Because one of the characteristics of low grade students is to think something is not important when they are unable to master or solve it. Therefore, guidance from the teacher is very important so that students are able to catch up and are willing to do something that they think is not important because the student cannot.